Public leadership development facilitation and the crossroads blues. Issue 4 (September 2015) - Smolović Jones, Owain; Grint, Keith; Cammock, Peter
The article seeks to make sense of the choices facing the public leadership development facilitator, in design and in-the-moment programme decisions. The challenge is posited as one of situating knowledge of facilitation practices in a critical relationship with the public sector leadership literature and the critical leadership development literature. The article positions public leadership development facilitation as sitting within three pressing dilemmas, or crossroads, concerning public leadership theory, critical leadership development scholarship and facilitation scholarship. A narrative ethnographic methodology is adopted to explore the constructions of a specific public sector leadership development facilitator as a means of analysing facilitator choices in action. An interpretation of how the facilitator frames and constructs public leadership in relation to the constructions of participants is offered. The article situates facilitator choices as highly political, sitting contextually between the idealism of the public sector literature and the social identifications of participants. The authors offer two dominant forms of facilitation choices (framing and adaptive) as a heuristic for facilitators, practitioners and scholars who wish to reflect further on the role of leadership development in the public realm.